PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 24 KUALA PENASO KEC. PINGGIR - Siti Hajijah Br. Siregar; Putri Yuanita; Zulkarnain Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract :This research aims to improve the learning process and improve learning outcomes mathematicsof fourth grade students of SDN 24 Kuala Penaso Kecamatan Pinggir by implementing cooperative learning model Two Stay Two Stray (TSTS). The research subjectswere fourth grade students who have theheterogeneous academic ability. This research is a class act with two cycles. The first cycle comprises four sessions with a one time UH in the end of each cycle, end the second cycle consists of two sessions with one time UH in every end of the cycle. As well as having four stages, are planning, implementation, observation and reflection, the results showed the activity of teacher and student has exhausted resources were well after done action. On a base score of students who reach the KKM is as much as 40% of the students achieved the first UH KKM as much as 60% and UH two students who achieve the KKM as much as 85%. The results of this study indicate that the application of cooperative learning model TSTS can improve the process of learning mathematics and improve learning outcomes of fourth grade students of SDN 24 Kuala Penaso Kecamatan Pinggir of the odd semester of the academic year 2013/2014.Keywords: Learning Process, Mathematics Outcomes Learning, Cooperative Learning, TSTS, Classroom Action Result.